Pengaruh Konten Food Vlogger Terhadap Minat Beli Calon Konsumen Gen-Z Provinsi DIY - Agatha Yesia Rustania; Dwi Maharani; Tri Puji Astuti (CV. ITTC INDONESIA, 2025)
This study examines the influence of food vlogger content on the purchase intention of Gen-Z consumers in the Special Region of Yogyakarta. The background of this research is based on the increasing consumption of culinary content on social media and the role of food vloggers as sources of information and consumption references. This study applies buyer motivation theory, which explains that external stimuli in the form of media content can trigger psychological responses that lead to purchase intention. The purpose of this study is to determine the extent to which food vlogger content affects the purchase intention of Gen Z consumers. A quantitative approach with a survey method was employed. Data were collected through Likert scale questionnaires from 102 Generation Z respondents who actively use social media and have watched food vlogger content. Data analysis was conducted using validity tests, reliability tests, and simple linear regression analysis. The results show that food vlogger content has a positive and significant effect on consumer purchase intention. The coefficient of determination indicates that food vlogger content accounts for 63.5 percent of the influence on purchase intention, while the remaining percentage is affected by other factors outside this study. These findings suggest that content quality, credibility, and interaction presented by food vloggers can effectively increase attention, understanding, and positive attitudes toward culinary products.